The Use of ICT Tools in Teaching English Literature : a Meta Analysis Study - Satya Monique Saragih; Ouda Teda Ena (EduInovasi: Journal of Basic Educational Studies, 2024)
This meta-analysis study explores the use of ICT (Information and Communication Technology) tools in teaching English Literature. It synthesizes findings from various previous studies to identify the positive impacts and challenges associated with the integration of ICT in literature classrooms. The results indicate that the use of ICT tools, such as interactive multimedia, e-learning platforms, and mobile applications, can enhance students' understanding of literary texts, enrich learning experiences, and increase student engagement. However, the success of this implementation heavily depends on the preparedness of teachers and the adequacy of technological infrastructure. The study concludes that while ICT has significant potential to transform the teaching of English Literature, proper training and ongoing support for educators are essential. Keywords: ICT, teaching English Literature, meta-analysis, e-learning, interactive multimedia, student engagement.